Sexual Behavior Surveys Should Ask More: Covering the Diversity of Sexual Behaviors That May Contribute to the Transmission of Pathogens. Issue 9 (17th September 2021) - Nagelkerke, Nico; Seedat, Shaheen; Abu-Raddad, Laith J.
Abstract : Supplemental digital content is available in the text.